Living with living systems: the co-evolution of values and valuation (2007)
This article explores features of the environmental valuation process through a coevolutionary approach. Based on established works concerning complexity, living systems, and social, economic, evolutionary and hierarchy theories, it is argued that a special form of recursive co-evolution takes place between articulated values and methods of value articulation, within the environmental valuation system. It is proposed that this co-evolutionary approach provides new insights into (1) the process of environmental preference formation and (2) the phenomenon of value incommensurability. Finally, it is suggested that this approach also reveals that monetary unit-based environmental valuation methods are counter-productive to their own purpose of ‘taking the economic worth of un-priced environmental goods and service into account.’ This constitutes a new critique of monetary valuation, which is not addressed by a pragmatic defence of the practice. It is suggested that, in lieu of monetary valuation, taking the economic worth of these phenomena into account may be better served by focusing efforts on the design of new value articulation methods that are capable of expressing their priceless economic worth.